The Influence of User Experience on Customer Engagement in Grab Application: A SERVQUAL Approach for Service Quality Evaluation - Hilda Aenussyifa; Arny Lattu; Moneyta Dholah Rosita (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
Digital transformation has fundamentally changed transportation services, yet existing research has predominantly applied traditional SERVQUAL frameworks without systematic integration with contemporary User Experience theories for Generation Z users. Limited research exists specifically investigating ride-hailing platforms among digital-native populations, creating a critical gap in understanding how generational characteristics influence service quality evaluation patterns. This study investigates the influence of User Experience (UX) on Customer Engagement (CE) in the Grab application among Generation Z users, utilizing the Service Quality (SERVQUAL) framework adapted for digital contexts. The research employed a quantitative approach with purposive sampling targeting 150 active Grab users aged 13-28 years who met specific usage criteria. Data collection utilized online questionnaires measuring five SERVQUAL dimensions, User Experience, and Customer Engagement variables through Likert scales, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results revealed fundamental shifts in how Generation Z users evaluate digital service quality. Among SERVQUAL dimensions, only visual interface elements (Tangibles) significantly influenced User Experience (β = 0.586, p = 0.001), while traditional interpersonal service dimensions showed no meaningful impact. User Experience demonstrated exceptionally strong influence on Customer Engagement (β = 0.945, p < 0.001), with the model explaining 89.3% of variance. These findings indicate that conventional service quality models require substantial adaptation for digital service contexts, particularly for Generation Z users who prioritize aesthetic design and interface functionality over traditional service elements. The study contributes to understanding how digital-native consumers evaluate technology-mediated transportation services, suggesting that service providers should focus primarily on user interface design and overall experience architecture to enhance customer engagement in the digital economy.